THE BONE MICROSTRUCTURE IDENTIFICATION MODEL BASED ON BACKSCATTER MODE OF ULTRASOUND - Umiatin Umiatin; Tora Oktaviana; Endang Wijaya; Riandini Riandini; Farhan Yusuf (Spektra: Jurnal Fisika dan Aplikasinya)
Osteoporosis is defined by a decrease in bone mass and a deterioration in bone microstructure. It is a major public health issue and a significant economic burden for both individuals and society. Thus, monitoring bone mass and structure is necessary to prevent bone fragility and osteoporosis. This study aimed to develop a prototype of quantitative ultrasound (QUS) and to evaluate the feasibility of backscatter mode for the bone assessment. Ultrasound (US) signals that propagate through the bone can be characterized by comparing the signal from both transmitter and receiver transducers. The US backscattered signal depends on the characteristic of both medium and transducer. In this study, we analyzed the attenuated signal based on the parameters: type of bone (compact and spongy), type of coupling medium (air, starch, and gel), the angle between transducers and bone (30o, 60o, and 90o), and transducer distance (0, 10, 5, 15, 20 and 25 cm). We use only 1 MHz transducer frequency. The prototype has been evaluated by Digital Oscilloscope and LabVIEW user interface to observe received signals. The results of this study showed that there was a difference in amplitude of the US signal from compact and spongy bones. The amplitude is directly proportional to acoustic impedance and inversely proportional to the distance between transducers. There is a negative correlation between bone microstructure to attenuation, and compact bones have a greater attenuation coefficient than spongy bones.